Evaluasi Ketahanan Genotipe Jagung Hibrida terhadap Penyakit Hawar Daun Maydis dan Karat Daun - Mirsam, Hishar; Suriani, Suriani; Djaenuddin, Nurasiah; Makkulawu, Andi Takdir; Abdullah, Fandi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Mirsam H, Suriani S, Makkulawu AT, Djaenuddin N, Abdullah F.Â 2021. Evaluation of resistance of hybrid corn genotypes against leaf blight and leaf rust diseases. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 305-313. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Plant pathogens are one of the causes of corn yield loss in Indonesia. Evaluation of the resistance of hybrid maize genotypes against major pathogens is deemed necessary as the first step in the management of the pathogens. This study aimed to evaluate the resistance reaction of the prospective hybrid corn varieties against the primary disease of corn. This study was conducted at two different locations. The location was at the Agricultural Technology Research and Assessment Installation (ATRAI) of the Indonesian Cereals Research Institute in Bajeng District, Gowa Regency, South Sulawesi. The study was conducted using spreader row plants as a source of inoculum for the test pathogen that planted around the experimental block. Spreader rows were inoculated with conidia suspension of the fungus Bipolaris maydis for leaf blight and the pathogen Puccinia polysora for leaf rust in the afternoon with a spore density of about 6 x104 conidia/ml. The results showed that there were 16 genotypes reacted moderately resistant and 7 genotypes reacted susceptible againstÂ B. maydis. In addition, there were 11 genotypes reacted moderately resistance and 12 genotypes that reacted susceptible against P. polysora.